2022
DOI: 10.1002/mrm.29235
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to MRI safety testing related to gradient‐induced heating of medical devices

Abstract: To theoretically investigate the feasibility of a novel procedure for testing the MRI gradient-induced heating of medical devices and translating the results into clinical practice. Methods:The concept of index of stress is introduced by decoupling the time waveform characteristics of the gradient field signals from the field spatial distribution within an MRI scanner. This index is also extended to consider the anisotropy of complex bulky metallic implants. Merits and drawbacks of the proposed index of stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…There is increasing interest in the role of gradient fields in inducing injuries in patients with large passive implants. There are several papers addressing potential concerns on the issue of excessive heating of implants from gradient fields in the clinical setting 8,9 . There is concern about the combined heating effects of strong radiofrequency and gradient fields in a clinical scanner 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing interest in the role of gradient fields in inducing injuries in patients with large passive implants. There are several papers addressing potential concerns on the issue of excessive heating of implants from gradient fields in the clinical setting 8,9 . There is concern about the combined heating effects of strong radiofrequency and gradient fields in a clinical scanner 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The depth of penetration (skin depth) of the currents and resulting heating depend on the frequency of the incident field, the resistivity, and magnetic permeability of the conductor 5,12 . A significant number of studies have been performed on the heating of parts or whole hip implants in tissues simulating gelled saline when exposed to gradient fields in clinical scanners, either experimentally or via computational modeling 1–9 . These demonstrate concerns about the safety of patients with passive implants due to gradient heating.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In GC scenarios, magnetic flux density and deposed power were assumed to be uniformly distributed inside the implant. Direct comparisons between experiments and computations, performed under the same hypothesis, showed a discrepancy less than 10% in the temperature increase both after relatively short exposures (20 s) [ 33 ] and after longer exposures (15 min) [ 34 ]. In addition, Wooldridge et al [ 23 ] showed that the total power deposed within a bulky orthopaedic implant correlated well with the temperature increase already after 360 s, independently of the actual power distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that the RF heating of the ASTM phantom is usually conservative with respect to the anatomical model, but sometimes, it greatly underestimates the thermal effects [ 36 ]. For the GC frequencies, Arduino et al [ 34 ], analysing two anatomical models with hip, knee, and shoulder prostheses, found that a phantom with ASTM gel thermal properties always underestimated the temperature increase with respect to the in vivo results. For this reason, the phantom was filled with a medium having the thermal properties of the bone, including perfusion (which plays an important role in steady-state thermal results) in order to try to better reproduce the local conditions of the implant in the human body.…”
Section: Discussionmentioning
confidence: 99%